2014
DOI: 10.1149/2.0161411jss
|View full text |Cite
|
Sign up to set email alerts
|

Very Low Temperature (Cyclic) Deposition / Etch of In Situ Boron-Doped SiGe Raised Sources and Drains

Abstract: We have developed an innovative 500°C process for the selective deposition of SiGe:B Raised Sources and Drains (RSDs). We have first of all studied on blanket Si wafers the in-situ boron doping of SiGe with Si2H6, GeH4 and B2H6. A growth rate increase by a factor higher than 4 together with a Ge concentration decrease from 45% down to 28% occurred as the diborane mass-flow increased (at 500°C, 20 Torr). Very high substitutional boron concentrations were achieved (∼5 × 1020 cm−3) in layers that were single crys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
19
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(26 citation statements)
references
References 28 publications
(40 reference statements)
6
19
1
Order By: Relevance
“…18 It was previously reported that in-situ doping of boron compensated for the compressive strain in the SiGe layer, and the Ge concentration calculated from the XRD results was lower than the actual quantity of Ge atoms. 19 In the present study, however, the SiGe peak shift from the undoped SiGe sample to the in-situ B-doped SiGe sample was 0.01 • . Thus, the effect of compensation was excluded from further discussions.…”
Section: Resultscontrasting
confidence: 69%
“…18 It was previously reported that in-situ doping of boron compensated for the compressive strain in the SiGe layer, and the Ge concentration calculated from the XRD results was lower than the actual quantity of Ge atoms. 19 In the present study, however, the SiGe peak shift from the undoped SiGe sample to the in-situ B-doped SiGe sample was 0.01 • . Thus, the effect of compensation was excluded from further discussions.…”
Section: Resultscontrasting
confidence: 69%
“…In addition, the advantages of incorporating an etching component into the deposition process were also demonstrated in early SEG research . More recently the advantages of cyclical deposition and etch processes for SEG have been demonstrated …”
Section: Motivation and Applications For Area-selective Depositionmentioning
confidence: 99%
“…109 More recently the advantages of cyclical deposition and etch processes for SEG have been demonstrated. 110 In its current form, SEG is an essential process in the formation of leading-edge metal oxide semiconducting field effect transistors (MOSFETs). 111 SEG is utilized in forming the source and drain of both N-type and P-type MOSFETs within the complementary MOS process flows used for advanced logic devices and SRAM memory.…”
Section: Systems-level Issues In Asd: Featurementioning
confidence: 99%
“…Disilane is however intrinsically non-selective versus dielectrics commonly used as spacer (Si 3 N 4 ) or isolation (SiO 2 ). This drawback can however be overcome with the addition of gaseous hydrochloric acid (or Cl 2 ) or the use of advanced (cyclic) deposition/etch (CDE) processes [9][10][11]. …”
Section: Introductionmentioning
confidence: 99%